(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This qualitative research study identified criteria for teacher quality preferences as perceived by current and past stu¬dents. A two-question, open-ended survey asking what qualities learners liked most and least in a teacher/presenter was given to two groups: students (Group A) from medicine, dentistry, and related residency programs; and dentists and physicians (Group B) who had graduated at least three years previously and who attended a minimum of two days of continuing education courses in lecture format each year. A total of 300 subjects provided 2,295 written responses. Descriptive words within the responses were coded and grouped according to similar relationships, resulting in the emergence of twenty-one defined categories that were fur¬ther refined into three core categories: personality, process, and performance. Results showed that the two groups appear to have different preferences in teacher/presenter characteristics. For Group A (students), the categories of content design, content orga¬nization, and content development were at the forefront of their preferences. Group B (professionals) overwhelmingly favored elements of speaker self-confidence and expertise. Both groups highly valued expertise and speaking style. These findings can be used to develop curriculum, enhance faculty members’ teaching skills, and plan continuing education programs.